Criminal Act of Destruction of Campaign Props of Candidates for dark election 2019 Gorontalo province - Mohamad Rama Perdana Tangahu (Estudiante Law Journal, 2020)
Abstract: This study aims to find out what factors are behind the perpetrators of the destruction of campaign props belonging to the Dprd Candidate in the 2019 General Election in The Gorontalo Province General Election Supervisory Agency and to find out how law enforcement efforts against criminals damage the campaign props of the DPRD Candidate in the 2019 General Election are reviewed from Law No. 7 of 2017 concerning general elections. The results of this study show: First,law enforcement efforts carried out by The Election Supervisory Agency together with gakumdu in handling election crimes against perpetrators of APK destruction in accordance with the applicable regulations as the provisions of Article 486 of Law No. 7 of 2017 concerning General Elections,  Election  Supervisory Agency  Gorontalo Province and Regency / City in handling findings / reports of alleged election crimes including destruction of APK then enforcement The law is carried out jointly with the police and prosecutors through the Integrated Law Enforcement Center (Sentra Gakkumdu);  Second,the factors behind the perpetrators doing damage to campaign props belonging to the DPRD Candidate in the 2019 General Election are (1) Weak awareness and knowledge of election law; (2) The existence of fanatical and anti-presidential behavior against certain Candidates / Election Participants; (3) The influence of liquor so that the perpetrators do damage to campaign props (billboards) belonging to one of the legislative candidates. Keywords: Destruction, APK, Legislative Member, Elections